ILRI's new priorities and direction of research and Development for livestock production in South-East Asia - Chantalakhana, C. (Japan International Research Center for Agricultural Sciences, 1998)
The economic importance and the role of livestock in sustainable agricultural systems in Southeast (SE) Asia is highlighted. The role of ILRI in international livestock research and relevance of ILRI's research priorities to future Development of livestock production in SE Asia are presented. In order to utilize available research resources most effectively and efficiently, ILRI has carried out very careful steps in the assessment of new priorities and direction of research and Development for livestock production in SE Asia. Process and approach used by ILRI to define such priorities and direction in Asia is briefly explained. It is very important for ILRi to build partnerships and to strengthen collaboration with Nars in SE Asia in order to achieve its ultimate goals in livestock research and Development in the region. ILRI research approach is based on multidisciplinary team with farming systems perspectives. For SE Asia such farming systems as crop-livestock systems in rainfed lowlands and tree crop-livestock systems in uplands have been identified since these farming systems are common to many countries in Asia. It has been clearly recognized by Asian Nars that international investment in livestock research in this region has been very limited. Increased investment from donor countries and organizations, especially those in Asia and Pacific region, will benefit not only the developing countries in SE Asia but also developed countries like Japan and others in an overall economic term.